STUDI PENDAHULUAN PENGEMBANGAN MEDIA PEMBELAJARAN ROLE PLAYING GAME (RPG) BERBASIS ANDROID PADA SISWA KELAS VII - Yuliana, Rosa; Salsabila, Ellis; Aziz, Tian Abdul (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Math is often thought to be a difficult subject, especially in solving problems. In addition, laziness while learning can cause various problems such as lack of understanding of concepts, problem solving skills. Therefore, the purpose of this research is to identify students' needs related to Android-based RPG learning media that can support students in learning math using a more creative and innovative way. This research uses a qualitative approach with a survey method through a data collection instrument in the form of a questionnaire. The research sample consisted of 30 students of SMP Negeri 217 Jakarta. Data collected from questionnaires were analyzed descriptively. The results stated that 70% of students felt the need to develop Android-based RPG learning media. The results of this observation provide an overview that can be used for the development of Android-based learning media using RPG.